Research of the quantitative content of liquefied gas by using model liquid systems - Білинський, Йосип Йосипович; Книш, Богдан Петрович; Юкиш, Марина Йосипівна (Technology audit and production reserves, 2014)
This paper presents the experimental research method for the choice of a liquid system model, which has a similar to liquefied petroleum gas structure, and also the determination of its temperature dependence. That makes it possible to verify the proposed thermometric method adequacy for quantitative content determining of the liquefied petroleum gas. This method allows to determine the quantitative content of not only the main mixture components (propane and butane) with different temperatures, but the content of impurities such as ethylene, propylene, butylene, amylene, heksylen, heptylen etc., which can improve the quantitative content accuracy of condensed petroleum gas components. Among the studied substances, such as toluene, isooctane, hexane, authors have found a compound that can be the optimal liquid system model and can be used as a reference based on which the density of liquefied petroleum gas and its quantitative value will be determined.